The Effect of Taking English Club Extracurricular Activity on Student’s Writing and Speaking Ability - Hernawan Simbolon; Sahlan Tampubolon; Arsen Pasaribu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The purpose of this study is to investigate the Effect of Taking English Club Extracurricular Activity on Student’s Writing and Speaking Ability at SMA St. Thomas 2Medan. The methodology of the research was Quantitative research. The technique of collecting the data are writing test and speaking test. The findings showed whether there were significant effects or not on students’ writing and speaking ability. The effect has been proved from the result of the pre-test and post-test. The researcher compared the result of the pre-test and post-test. If the result of the post-test was higher than the pre-test, it meant that English club extracurricular activity was affected. The writing result shows the difference between the mean score of the pre-test and post-test after conducting treatment where the mean score of students’ writing ability on the pre-test is 5,79 and the post-test is 8,47. After analysing the result of the pre-test and post-test by using a formula, it has gotten a percentage of about 46,28 % of students’ improvement. It indicates that applying English Club Extracurricular Activity is effective to be used in learning writing and in Speaking ability, the result  shows the difference between the mean score of the pre-test and post-test after conducting treatment where the mean score of students’ speaking ability on the pre-test is 3,05 and the post-test is 4,76. After analysing the result of the pre-test and post-test by using a formula, it has gotten a percentage of about 56,06 % of students’ improvement. Based on the result of data analysis, the researcher concludes that applying English Club Extracurricular Activity is effective in improving the students’ writing and speaking skills